The self as muse : narcissism and creativity in the German imagination, 1750-1830 - Mathäs, Alexander, 1951- (Transits (Bucknell University), 2011)
While there are countless philosophical and psychological studies that focus on sources of the self, narcissism - the creation of an ideal image of the self and the vain attempt to merge with it - has found relatively little attention in a pre-Freudian context. The Self as Muse fills this gap by examining various aspects of narcissism and their significance for the outpouring of creativity in late eighteenth and nineteenth-century German literature. Narcissism provided an impetus for poetic production when writers expressed what they perceived as the inner workings of their soul. By showing na.